Epidemiology of Bluetongue Virus and Epizootic Hemorrhagic Disease Virus in Beef Cattle on a Ranch in South-Central Florida - Merrill, Mary M. (Vector Borne Zoonotic Dis, 2019)
Bluetongue virus (BTV) and epizootic hemorrhagic disease virus (EHDV) infect a variety of wild and domestic ruminant hosts in the United States, with outcomes ranging from subclinical infection to clinical disease resulting in mortality. Because cattle have been suggested as a temporary reservoir for both BTV and EHDV, ongoing national surveillance for these viruses may benefit from inclusion of domestic cattle as a supplement to current programs, such as surveillance of wild white-tailed deer. To better understand the prevalence of BTV and EHDV in cattle, we surveyed for viral RNA (vRNA) in the blood of 1,604 beef cattle on a south-central Florida cattle ranch over 3 years. While overall prevalence of vRNA in blood was low (<2% for either virus), the occurrence of vRNA was much higher in young animals: in 2016, 24% of animals 2 years old were positive by PCR for either BTV or EHDV. Our results suggest that cattle are a likely temporary reservoir for these viruses in Florida, and could provide additional information on the spatial distribution, viral diversity, and timing of emergence of these viruses, particularly if surveillance was restricted to cattle ≤2 years of age.